PENGARUH MODAL SENDIRI, MODAL ASING, DAN VOLUME USAHA TERHADAP SISA HASIL USAHA PADA KOPERASI UNIT DESA (KUD) DI KABUPATEN MALANG PERIODE 2013-2017 - Muhammad Fadllun Niam; M. Agus Salim; Afi Rachmat Slamet (E-JRM : Elektronik Jurnal Riset Manajemen, 2018)
ABSTRACTThis research is based on the growing development of cooperatives at this time, the demand for good and professional management of cooperatives is getting bigger. The purpose of this research is to find out and analyze whether there is an influence of the relationship of equity capital X1, equity X2, business volume X3, while the variable Y is the remaining business results. this study uses quantitative methods. The results showed that there was a significant influence between own capital, foreign capital and business volume on the remaining business results, so as to increase the remaining business results by increasing capital and increasing business volume. Keywords : Village Unit Cooperatives, Own Capital, Foreign Capital, Business               Volume,Remaining Business Results.